Pesticides in vitro interference in the germination and in the tube pollinic germination and elongation in the tomato plant Cultivar Santa Cruz kada - de Lacerda, Cynthia Araújo; de Lima, José Oscar Gomes; de Almeida, Élcio Cruz; de Oliveira, Laede Maffia (Pesquisa Agropecuaria Brasileira, 1994)
The germination of pollen and tube elongation of tomato (Lycopersicon esculentum Mill.), on artificial medium were drastically reduced by dry residues of chlorothalonil 75% WP (3.200 ppm of a.i.), mancozeb 80% WP (2.400 ppm of a.i.), mancozeb 48% WP (1.680 ppm of a.i.) + metalaxyl 10% WP (350 ppm of a.i.), and dibrom 86% EC (1.030 ppm of a.i.). Cartap 50% SP (600 ppm of a.i.) had no effect upon pollen germination but reduced tube elongation by 38.2% in relation to control. the spreaders stickers, alkyl phenol ethoxylate 25% AS (70 ppm of a.i.) and naphthenic hydrocarbons + ethoxylate compounds 86% - (1.720 ppm of a.i.), and the insecticides abamectin 1.8% EC (300 ppm of a.i.), deltamethrin 2.5% EC (10 ppm of a.i.), methamidophos 60% LC (600 ppm of a.i.), and permethrin 50% EC (100 ppm of a.i.) were noninjurious to pollen.